Bowel cancer screening is safe, detects earlier stage cancer and adenomas in 50% of cases: experience of the prevalent round of screening from two first wave centres in the North East of England. Issue 1 (28th October 2011) - Rajasekhar, P T; Clifford, G M; Lee, T J W; Rutter, M D; Waddup, G; Ritchie, M; Nylander, D; Painter, J; Singh, J; Ward, I; Dempsey, N; Bowes, J; et al.
Abstract : Objective: The NHS Bowel Cancer Screening Programme (BCSP) began roll-out in 2006 aiming to reduce cancer mortality through detection at an earlier stage. We report results from the prevalent round of screening at two first wave centres and compare with the UK pilot study. Design: This is a service evaluation study. Data were collected prospectively for all individuals undergoing faecal occult blood testing (FOBt) and colonoscopy including: uptake and outcomes of FOBt, colonoscopic performance, findings, histological data and complications. Continuous data were compared using a two-tailed test of two proportions. Setting: The South of Tyne and Tees Bowel Cancer Screening centres. Patients: Participants of the BCSP. Main Outcome Measures: 1) Colonoscopy Quality Assurance and 2) Cancer stage shift. Results: 195, 772 individuals were invited to participate. Uptake was 54% and FOBt positivity 1.7%. 1524 underwent colonoscopy with caecal intubation in 1485 (97%). 180 (12%) cancers were detected. Dukes stages were: 76 (42%) A; 47 (26%) B; 47 (26%) C; 8 (4%) D and 2 (1%) unknown. This demonstrates a significantly earlier stage at diagnosis compared with data from 2867 non-screening detected cancers (p<0.001). Adenomas were detected in 758 (50%). One perforation occurred (0.07%) and two intermediate bleeds requiring transfusion only (0.12%). Both caecal intubation and adenoma detection were significantly higher than in the UK pilot study (p<0.001). Conclusions: The prevalent round of screening demonstrates a high adenoma and cancer detection rate and significantly earlier stage at diagnosis. Complications were few providing reassurance regarding safety. Efforts are required to improve uptake.